A Survey of Scholarship on Paul’s Temple Language in 1 Corinthians - Park, Jason; Rosner, Brian S. 1959- (2025)
The temple metaphor occupies a central place in 1 Corinthians. It appears in two chapters and is closely connected to several recurring themes across the letter. Both Jews and non-Jews in Paul’s audience had strong associations and experience with temples. In this article, we review how scholars have envisaged how Paul contextualized his message in this ethno-cultural and religious context. We also review studies on the connections that Paul’s temple motif has with other metaphors in the letter, such as wisdom, field, building, and body, and how they tie in together around the key themes, such as holiness and glory.
Keywords: Qumran; Old Testament; Glory; Holiness; Graeco-Roman temples; temple metaphor; 1 Corinthians